Are all regions of folded proteins that undergo ligand‐dependent order–disorder transitions targets for allosteric peptide mimetics?. Issue 6 (November 2013) - Fenton, Aron W.; Gierasch, Lila; Lynn, David; Schneider, Joel
ABSTRACT Although the classical view of how proteins function relied on well folded structures, it is now recognized that the functions of many proteins are dependent on being intrinsically disordered. The primary consideration in this work is the intermediate group of proteins that are overall well folded, but which contain small regions that undergo order–disorder transitions. In particular, the current focus is on those order–disorder transitions that are energetically coupled to ligand binding. As exemplified by the case of human liver pyruvate kinase (hL‐PYK), peptides that mimic the sequence of the order–disorder region can be used as allosteric regulators of the enzyme. On the basis of this example and others reported in the literature, we propose that a similar use of peptides that mimic protein regions that experience ligand‐dependent order–disorder transitions can be a generalized initiation point for the development of allosteric drugs. © 2013 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 100: 553–557, 2013.